De boswachter van de bloemen : De bescherming van de orchideeën en de Natuurbeschermingswacht Zuidoost-Limburg - Mennen, Kristian (Studies over de sociaaleconomische geschiedenis van Limburg, 2025)
Since the end of the nineteenth century, tourists and scientific botanists discovered the nature, landscape and scenery of the south of the province of Limburg. Rare orchids were among the main attractions, but these species became endangered because of excessive visits and picking. This article focusses on three groups of conservationist actors and two strategies to protect the wild orchids. The national and regional conservationist organisations adopted a top-down strategy: they approached the province administration and the municipalities in the region, until the latter agreed to ban the picking of wild orchids in 1948. Because the leaders of the conservationist movement started to realise that such a top-down approach was not conducive to the popular support of conservationist ideas, bottom-up groups were set up to spread conservationist ideas at the local level. One such groups was the Natuurbeschermingswacht Zuidoost-Limburg, founded in Heerlen in 1948, with the express aim to guard the protected orchid areas. The Natuur- beschermingswacht’s membership was a mix of different generations, of academically trained experts and ‘ordinary’ people from Heerlen and its surrounding region. The protection of wild orchids successfully combined the top-down ban to pick orchids and the bottom-up initiative to administer and control that ban.